2021
DOI: 10.1093/ndt/gfab179
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis patients show a highly diminished antibody response after COVID-19 mRNA vaccination compared with healthy controls

Abstract: Background Haemodialysis (HD) patients are exposed to a high risk due to the SARS-CoV-2 pandemic. They are prone to acquiring the infection and are threatened by high mortality rates in case of infection. However, HD patients were not included in the efficacy trials of the SARS-CoV-2 vaccines. Such efficacy data would have been critical because HD patients show decreased responses against various other vaccines and this could translate to the SARS-CoV-2 vaccines as well. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
130
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(148 citation statements)
references
References 28 publications
13
130
4
1
Order By: Relevance
“…This observation is of interest given that antibody titres are described as significantly lower in HD patients after vaccination as compared with healthy subjects [ 5 , 8 , 14 , 15 ] and that a lower antibody response is associated with a lower ability to neutralize SARS-CoV-2 in vitro [ 14 ]. Additionally, a recent study demonstrated that a rapid decline of anti-SARS-CoV-2 antibodies occurs following natural immunization after COVID-19 in dialysis patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This observation is of interest given that antibody titres are described as significantly lower in HD patients after vaccination as compared with healthy subjects [ 5 , 8 , 14 , 15 ] and that a lower antibody response is associated with a lower ability to neutralize SARS-CoV-2 in vitro [ 14 ]. Additionally, a recent study demonstrated that a rapid decline of anti-SARS-CoV-2 antibodies occurs following natural immunization after COVID-19 in dialysis patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the strategy to eliminate COVID-19 is based on mass vaccination campaigns. Thus, a better awareness of the immune responses to SARS-CoV-2 infection in immunodepressed populations is also important to optimize vaccination strategies in such weak patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…Robust SARS-CoV-2 antibody responses ≥7 days after the second dose were detected (4). However, patients with KF have an impaired response to vaccination (5) and the earliest reports on COVID-19 vaccination suggest that mRNA vaccines are immunogenic but some patients on dialysis do not seroconvert (6)(7)(8). Patients on kidney replacement therapy were excluded from previous trials.…”
Section: Introductionmentioning
confidence: 99%